Paleogene granite magmatism in the north of the Truong Son belt and implication for crustal evolution - Trinh Dinh, Huan; Luu Cong, Tri; Nguyen Tuan, Anh; Tran Viet, Anh; Phan Hoang, Giang; Takahashi; Saadsy (Vietnam Journal of Earth Sciences, 2021)
Abundant granitoids aged 24.59 Ma to 28.62 Ma were exposed along Phu Hoat high metamorphic zone, northern of the Truong Son belt, termed Na Khoun complex in Northern Laos (NL) and Ban Chieng complex in Western Vietnam (WV). Ten granitic samples were collected from these complexes show geochemical characteristics of high SiO2 and K2O contents, medium peraluminous that belong to S-type granites. Initial 87Sr/86Sr isotopic ratios and εNd(t) are broad values of 0.708507 to 0.74539 and -5.22 to -12.66, respectively, together with high 206Pb/204Pb (18.864-19.392), 207Pb/204Pb (15.736-15.841) and 208Pb/204Pb (39.224-40.080) which indicated crustal origin, we suggest that the NL-WV intrusion was associated with transpression form by the India-Asia collision events during Cenozoic.